2020
DOI: 10.1111/ejss.12921
|View full text |Cite
|
Sign up to set email alerts
|

Limited effects of depth (0–80 cm) on communities of archaea, bacteria and fungi in paddy soil profiles

Abstract: Most current microbial studies in paddy soils have focused on the top (0–20 cm) layer where rice roots are concentrated. To better understand the vertical distribution of microorganisms in paddy soils, we investigated the abundances, diversities and community compositions of archaea, bacteria and fungi in six geographically and climatically distinct paddy soil profiles from 0–80‐cm depth. Although microbial abundances and operational taxonomic unit (OTU) diversities largely decreased with soil depth, only the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
4
9
0
Order By: Relevance
“…Soil organic carbon and TN contents decreased with the soil horizon, which was consistent with the findings of Yuan et al ( 2020 ) and Li W. et al ( 2022 ). In this study, SOC and TN contents were higher in the 0–20-cm soil horizon than in the 20–120- and 70–120-cm soil horizons.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Soil organic carbon and TN contents decreased with the soil horizon, which was consistent with the findings of Yuan et al ( 2020 ) and Li W. et al ( 2022 ). In this study, SOC and TN contents were higher in the 0–20-cm soil horizon than in the 20–120- and 70–120-cm soil horizons.…”
Section: Discussionsupporting
confidence: 91%
“…Studies on the variability of prokaryotic community composition and functional groups have been more biased toward surface soils, but little is known about its response in the deep layer (Eilers et al, 2012 ; Yuan et al, 2020 ). Ancient rice terraces have experienced hundreds of years of management measures (repeated tillage and fertilization), as well as long-term leaching and enrichment effects, resulting in significant soil horizons in the profile (Gong, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…As reflected by Figure 4 b, however, Pielou’s evenness index was slightly higher in top soil (1–3 m) than in subsoil (4–10 m). As shown in Table S2 , the diversity indexes were impacted by soil properties and the contents of metal(loid)s, indicating environmental conditions, such as pH, TK, CEC, ORP, and Bio-Cu ( p < 0.05), impacted the soil microbial evenness through limiting the survival of certain microorganisms [ 27 , 28 ]; while, soil microbes adapt to higher metal(loid)s pollution in top soil by changing microbial communities, rather than changing their evenness [ 29 ]. Moreover, Shannon’s diversity index and Simpson’s index of diversity exhibited a decreasing trend from 1 m to 10 m of soil depth, which might be ascribed to the decrease in evenness with increase in depth, as shown in Figure 4 c,d.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial diversity generally decreased towards deeper soil, while archaeal diversity increased along with soil depth in the desert ( Wang et al, 2021 ) and alpine ecosystems ( Xu et al, 2021 ). However, others reported that bacterial and archaeal richness negatively correlated with soil depth in paddy soils ( Yuan et al, 2020 ). The varying conclusions of these studies emphasize the need for further comparisons between the vertical distribution patterns of archaeal and bacterial communities.…”
Section: Introductionmentioning
confidence: 99%